Pedodontics and preventive dentistry as career option: post graduate student’s perspective - S., Sultan (International Journal of Research in Medical Sciences, 2018)
Background: In dentistry choosing a postgraduate branch after bachelor’s degree is quite complex and difficult, as all specialties have their own significance and application. In such situation dental graduate should evaluate his own capability and interest rather than any pressure or persuasion from his friends or parents and hence accordingly make his selection for post-graduation specialization. The ambitions of an aspiring candidate in a particular specialty in turn contribute a lot for the future of that specialty especially in pedodontics which has the responsibility of detecting and early intervention regarding dental caries and other oral health related problem. The aim and objective of this study was to evaluate the reasons of post graduate students in private and government dental colleges in India for selection pedodontics and preventive dentistry as career after completing graduation. Methods: A questionnaire-based study was conducted among 100 students pursuing post-graduation in pedodontics and preventive dentistry. The questionnaire consisted of eight close ended and one open ended items which included career choice-related questions and demographic (age and gender) data. Finally, data was collected and presented as frequency distribution. Results: Overall majority of students choose pedodontics as choice about 65% (65/100) and 35% (35/100) were those who got in pedodontics field by chance. 15% (15/100) students had family role in getting MDS admission in pedodontics. Conclusions: Post graduate pedodontics students mostly have chosen pedodontics as a professional career due to their personal interest and influence of family and those who by chance opted pedodontics developed interest in the subject with time.